A Philosophical commentary of happiness among Kawangware and Kibera youth using Spitzer’s theory - Oyugi, Cynthia Achieng (Strathmore University, 2019)
What is happiness? This concept has plagued man from the ancient times; and even today in the contemporary 21st Century. This is because there are different ways of understanding what happiness is. Youth are the future; their concept of happiness is therefore vital for creating a happy society. Spitzer ranks pleasure as level one of happiness and achievement as level two of happiness; however, Spitzer argues that the fulfilment of the desires of pleasure (H1) and achievement (H2) does not yield true happiness in man. Spitzer ranks contribution and transcendence respectively as level three of happiness (H3) and level four of happiness (H4). Spitzer emphasizes that true happiness in man includes ‘contribution’ and ‘transcendence’ as well as ‘pleasure’ and ‘achievement’ because ‘none of the levels should be neglected’. The main aim of this MAPE research study was to determine Spitzer components of happiness among Kawangware and Kibera youth. The MAPE researcher therefore administered a questionnaire to 100 Kawangware youth and 560 Kibera youth; the questions were based on Spitzer’s theory of happiness and were analysed using SPSS. The research study findings confirmed Spitzer’s theory that true happiness for man comprises ‘pleasure’, ‘achievement’, ‘contribution’ and ‘transcendence’ because all four aspects of happiness were exhibited by Kawangware and Kibera youth. The researcher argues that the inclusion of ‘contribution’ and ‘transcendence’ is important because they are both compatible with ethical actions; since ‘contribution’ embraces virtue as well as the common good, and ‘transcendence’ embraces God. 75.5% of study participants reported happiness is always found when contributing positively to society; since they want to make a difference in the world and because it is a moral duty; this is consistent with Spitzer’s component of contribution. Finally 97.9% of study participants reported happiness is always found in God which is compatible with Spitzer’s component of Transcendence. According to the researcher, these research findings are encouraging since it implies a willingness of Kawangware and Kibera youth to constantly engage in virtuous actions.
Thesis submitted in partial fulfillment of the requirements for the Degree of Masters in Applied Philosophy and Ethics (MAPE) at Strathmore University, Kenya
Keywords: Philosophical commentary; Kawangware and Kibera youth; Spitzer’s theory; Happiness